Astrocytes Modify Migration of PBMCs Induced by β-Amyloid in a Blood-Brain Barrier in vitro Model - Spampinato, Simona Federica; Merlo, Sara; Fagone, Evelina; Fruciano, Mary; Barbagallo, Cristina; Kanda, Takashi; Sano, Yasuteru; Purrello, Michele; Vancheri, Carlo; Ragusa, Marco; Sortino, Maria Angela (Frontiers in Cellular Neuroscience, 2019)
Background: The brain is protected by the blood-brain barrier (BBB), constituted by endothelial cells supported by pericytes and astrocytes. In Alzheimer’s Disease a dysregulation of the BBB occurs since the early phases of the disease leading to an increased access of solutes and immune cells that can participate to the central inflammatory response. Here we investigated whether astrocytes may influence endothelial-leukocytes interaction in the presence of amyloid-β (Aβ). Methods: We used an in vitro BBB model, where endothelial cells, cultured alone or with astrocytes were exposed for 5 h to Aβ, both under resting or inflammatory conditions (TNFα and IFNγ), to evaluate endothelial barrier properties, as well as transendothelial migration of peripheral blood mononuclear cells (PBMCs). Results: In the co-culture model, barrier permeability to solutes was increased by all treatments, but migration was only observed in inflammatory conditions and was prevented by Aβ treatment. On the contrary, in endothelial monocultures, Aβ induced leukocytes migration under resting conditions and did not modify that induced by inflammatory cytokines. In endothelial astrocyte co-cultures, a low molecular weight isoform of the adhesion molecule ICAM-1, important to allow interaction with PBMCs, was increased after 5 h exposure to inflammatory cytokines, an effect that was prevented by Aβ. This modulation by Aβ was not observed in endothelial monocultures. In addition, endothelial expression of β-1,4-N-acetylglucosaminyltransferase III (Gnt-III), responsible for the formation of the low molecular weight ICAM-1 isoform, was enhanced in inflammatory conditions, but negatively modulated by Aβ only in the co-culture model. miR-200b, increased in astrocytes following Aβ treatment and may represent one of the factors involved in the control of Gnt-III expression. Conclusions: These data point out that, at least in the early phases of Aβ exposure, astrocytes play a role in the modulation of leucocytes migration through the endothelial layer.